2019
DOI: 10.3889/oamjms.2019.643
|View full text |Cite
|
Sign up to set email alerts
|

Copeptin as a Biomarker of Atherosclerosis in Type 1 Diabetic Patients

Abstract: AIM: To evaluate copeptin as an early marker of atherosclerosis in adolescent type 1 diabetics. METHODS: Sixty-two type 1 diabetic patients and 50 healthy volunteers were enrolled in the study. Serum copeptin, glycosylated haemoglobin (HbA1c), lipid profile, oxidised low-density lipoprotein (OxLDL), urinary albumin/creatinine ratio, carotid intimal medial thickness (cIMT), aortic intimal medial thickness (aIMT) and resistivity index were assessed for all participant in the study. RESULTS: HbA1, alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Our finding is in agreement with Wang and colleagues [21] who found no significant difference in copeptin levels between subjects with normal carotid artery duplex and those who had higher carotid artery intima-media thickness. Unlike El Dayem and colleagues [28], who concluded that copeptin is an inflammatory marker and associated with increase in carotid artery intima-media thickness and can be a predictor for atherosclerosis. The difference between our findings and that of El Dayem and colleagues can be explained by the difference in patient groups, as all the patients included in El Dayem and colleagues study were diabetics, while only 35.6% of our patients were diabetic, many studies elaborated higher copeptin levels in diabetic patients as discussed before.…”
Section: Discussionmentioning
confidence: 79%
“…Our finding is in agreement with Wang and colleagues [21] who found no significant difference in copeptin levels between subjects with normal carotid artery duplex and those who had higher carotid artery intima-media thickness. Unlike El Dayem and colleagues [28], who concluded that copeptin is an inflammatory marker and associated with increase in carotid artery intima-media thickness and can be a predictor for atherosclerosis. The difference between our findings and that of El Dayem and colleagues can be explained by the difference in patient groups, as all the patients included in El Dayem and colleagues study were diabetics, while only 35.6% of our patients were diabetic, many studies elaborated higher copeptin levels in diabetic patients as discussed before.…”
Section: Discussionmentioning
confidence: 79%
“…Copeptin is a peptide which derives from the same precursor of arginine vasopressin and is considered a useful biomarker of several pathologic conditions such as myocardial infarction, atherosclerosis and ischemic stroke [ 66 ]. Recent observational studies have discovered that higher blood levels of copeptin are strictly associated with the development of atherosclerosis, arterial stiffness and kidney damage in patients with type 1 diabetes [ 67 , 68 ]. In particular, patients with the highest levels of copeptin have concomitantly increased levels of albuminuria, the main marker of kidney damage [ 69 ].…”
Section: Biomarkers and New Tools To Improve Individual Risk Predicti...mentioning
confidence: 99%